South African Consumer Perspectives on Electronic Contract Challenges and Legislative Implications - Nikita Dwarika; Karunanidhi Reddy (Contemporary Issues of Business and Management: The Proceedings of the \(10^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
In recent years, the rise of online shopping and electronic contracts has intensified the challenges faced by South African consumers. This study investigates these challenges, emphasising the role of South Africa’s Consumer Protection Act (CPA) and Electronic Communications and Transactions Act (ECTA) in safeguarding consumers. Focusing on fairness and accessibility, this study identifies and explores barriers to consumer understanding, enforceability, and awareness, particularly in light of consumer rights such as transparency, privacy, and informed consent. Key findings reveal the need for greater transparency and simplification of contract terms. This research employs multiple methods, combining a consumer survey with quantitative analysis to explore gaps in consumer awareness and regulatory effectiveness. The study utilised non-probability sampling techniques, employing purposive and convenience sampling. The consumer survey, which was primarily quantitative in nature, utilised questionnaires. Limited research has been conducted on electronic contract consumer challenges in South Africa and studies have focused more on formal face-to-face written agreements. This study therefore addresses such gap by exploring online consumer challenges and the protection provided by existing consumer laws. The findings show that there are multiple challenges and barriers facing consumers with respect to electronic contracts, notably, revealing significant challenges in consumer understanding, a lack of accessible contract language, and barriers to enforceability that have not been adequately addressed. In addition, possible measures to address such challenges include workshops on consumer protection laws and consumer contracts in plain and understandable language.